Trophic structure of macroinvertebrates in Amazonian streams impacted by anthropogenic siltation - Couceiro, Sheyla R.M. (Austral Ecology, 2020)
This study assessed the results of anthropogenic sediment input on macroinvertebrate trophic structure in streams located in an area of oil and natural gas exploitation in Brazil's Amazon forest. The results indicate that macroinvertebrate communities both in streams impacted by anthropogenic sediments and in non-impacted streams are composed mainly of taxa in the following functional feeding groups: predators, gathering-collectors, scrapers, shredders and filtering-collectors. The highest densities were observed for collector-gatherers, followed by scrapers, predators, shredders and filtering-collectors. However, both the richness and the density of all groups were reduced in impacted streams. The reductions were significantly related to suspended inorganic sediment load and to the colour of suspended sediments. The relative proportion of shredders in streams impacted by anthropogenic sediments was significantly reduced as compared with the proportion observed in non-impacted streams. This resulted from lower availability of coarse particulate organic matter in these streams owing to burial of leaves and other plant material. These results indicate changes in the functioning and productivity of streams owing to anthropogenic siltation. This is because the benthic macroinvertebrate communities, sampled during this study, were dependent on the degradation of leaves, which are the primary energy source sustaining the benthic foodweb. © 2010 The Authors. Journal compilation © 2010 Ecological Society of Australia.